The Wire - The Complete Third Season Episode 1-12 - Bianchi, Edward; Holland, Agnieszka; Dickerson, Ernest; Briesewitz, Uta; Egilsson, Eagle; West, Dominic; Doman, John; Elba, Idris (Warner, 2005)
In chronicling a multi-generational family business dealing illegal drugs and the efforts of the Baltimore police to curb their trade, this series draws parallels between these organizations and the men and women on either side of the battle ... Season Three investigates politics and finishes the main stories that were left open in season one. [www.tv.com]
Keywords: DVD-Video